Landscape-level effects on developmental instability: fluctuating asymmetry across the range of honey locust, Gleditsia triacanthos (Fabaceae) - Murphy, H.T; Lovett-Doust, J (International journal of plant sciences, 2004)
Developmental instability is typically measured as patterns of fluctuating asymmetry (FA), small departures from perfect symmetry in structural morphology. Although the mechanisms producing developmental instability remain unclear, the disruptive effect of “stressors” during development is assumed to induce deviations from symmetrical phenotypes. Associations between developmental stress and FA are particularly interesting from the general perspective of fragmented and marginal populations, which are thought to be exposed to greater levels of genetic and environmental stress. We measured two leaf FA parameters at 18 populations across the range of the native treeGleditsia triacanthos(honey locust). Highly significant effects of both landscape (region) and site were found for the two FA traits. FA did not generally increase in geographically marginal populations nor was either FA index correlated with latitude or climatic factors. FA also did not generally increase in smaller populations, and it was not related to site elevation or conspecific tree density at sites. These results indicate either that honey locust trees are not subject to greater environmental or genetic stress in fragmented or marginal populations or that FA is not a reliable indicator of stress.